Serologic Testing for Syphilis: Benefits and Challenges of a Reverse Algorithm - Soreng, Katherine; Levy, Roma; Fakile, Yetunde (Clinical microbiology newsletter, 2014)
Syphilis is a human infection of global importance. Its diagnosis can be challenging, requiring construction of a serologic profile based on the results of at least two types of antibody tests: treponemal and nontreponemal. The traditional approach to the serodiagnosis of syphilis has been the use of a nontreponemal screening assay followed by the performance of a treponemal confirmatory test if the initial nontreponemal screening test was reactive. With the increasing availability of automated, easier-to-perform, and rapid treponemal assays, an increasing number of laboratory testing sites are adopting reverse sequence screening for the serodiagnosis of syphilis: screening with a treponemal assay first, then confirmation with a nontreponemal assay and, when necessary, discrepant resolution using another treponemal test. In addition to offering automation and increased throughput, a reverse algorithm can increase disease detection, especially in late latent and early primary stages of infection when the nontreponemal antibody test may be nonreactive. However, a disadvantage to this approach is that there can be an increase in false-positive test results. This article reviews the clinical and workflow benefits and limitations of a reverse testing algorithm and discusses current guidance available from the Centers for Disease Control and Prevention.